Biological variation of cardiovascular biochemical markers in patients with Type 2 Diabetes Mellitus - Wang, Xia; Zeng, Yuping; He, He; Zhang, Mei; Li, Chuan; Yang, Lidan; Chen, Jie; Huang, Hengjian (Clinica chimica acta, 2022)
•There is an inconsistency in BV values between healthy populations and T2DM patients we studied.•Population-based reference intervals should be used with caution in clinical decision-making in T2DM patients.•Sex as a biological variable in CVD is critical to future precision medicine strategies in clinical trials.•These data help to correctly interpret cardiovascular biomarker levels in T2DM patients. Type 2 diabetes mellitus (T2DM) is a well-established risk factor for cardiovascular diseases. We aimed to identify the biological variation of ten cardiovascular biochemical markers in T2DM patients to aid in their interpretation. Blood samples for evaluating ten biomarkers were collected biweekly from 23 T2DM patients (10 men, 13 women) for three months. The analytical variability and variations of within-subject (CVI) and between-subject (CVG) levels were calculated, as well as the analytical performance specifications, reference change value (RCV), and index of individuality (II). The levels of total cholesterol (CHOL), apolipoprotein A (apoA), homocysteine (HCY), high-sensitivity troponin T (hsTnT) and N-terminal pro-brain natriuretic peptide (NT-proBNP) differed between males and females (P < 0.05). The CVIs or CVGs of the biomakers were higher than those of healthy participants in Westgard online database, except for hsTnT. Triglyceride (TG), lipoprotein (a) [Lp(a)] and NT-proBNP had relatively high CVI, CVG and RCV, whereas CHOL, high-density lipoprotein cholesterol (HDL-C), apoA and HCY showed low variation. Moreover, the II of HDL-C, LP(a), apoA, HCY and hsTnT was <0.6 and other biochemical markers was between 0.6 and 1.4. The cardiovascular biochemical markers in T2DM patients showed higher CVI or CVG, except for hsTnT. ApoA had the lowest CVI and CVG values. Population-based reference intervals should be used with caution in clinical decision-making for T2DM patients.